Impact of NHI copayment adjustments on healthcare seeking behavior: the mediating role of health facility identification - Liang-Hsi Kung; Chih-Ming Kung; Chien Chih Chen; Yu-Hua Yan (BMC, 2024)
Abstract Objective This study investigates the impact of healthcare consumers' involvement, price perception, and attitude toward National Health Insurance (NHI) copayment adjustments on their healthcare-seeking behavior, focusing on the mediating role of health facility identification. Methods A questionnaire survey was conducted among outpatient customers in Taiwan from October 2023 to March 2024, resulting in 746 valid responses. The survey included demographic variables, involvement, price perception, attitude, health facility identification, and healthcare-seeking behavior. Data were analyzed using descriptive statistics, correlation analysis, and multiple regression analysis with SPSS 20.0. Results The study found that involvement, price perception, and attitude significantly influence healthcare-seeking behavior. Health facility identification was identified as a significant mediator in the relationship between copayment perception and healthcare-seeking behavior. The regression analysis also highlighted the impact of demographic factors such as age, education level, marital status, and annual income on healthcare-seeking behavior. The path model illustrated the complex interplay between perceptual factors and their influence on healthcare-seeking behavior. Conclusion This study emphasizes the importance of consumer involvement, price perception, and attitude in shaping healthcare utilization patterns. Health facility identification plays a crucial mediating role, suggesting that stronger patient-provider relationships can mitigate potential negative impacts of copayment adjustments. Policymakers and healthcare providers should enhance patient engagement, foster strong patient-facility identification, and provide targeted support for vulnerable groups to ensure equitable access to healthcare services despite copayment changes.